Toxicological evaluation of porcine bile powder in Kunming mice and Sprague–Dawley rats - Wu, Lirong; Wang, Jieyi; Lei, Jing; Ge, Kun; Qu, Chun; Liu, Jiajian; Huang, Fengjie; Sun, Dongnan; Chao, Xiaowen; Chen, Tianlu; Zhao, Aihua; Jia, Wei; et al. (Frontiers in Pharmacology, 2024)
Background: Porcine bile powder (PBP) is a traditional Chinese medicine that has been used for centuries in various therapeutic applications. However, PBP has not previously undergone comprehensive component analysis and not been evaluated for safety through standard in vivo toxicological studies. Methods: In our study, we characterized the component of PBP by liquid chromatography-mass spectrometry. The acute and subchronic oral toxicity, genotoxicity, and teratogenicity studies of PBP were designed and conducted in Kunming mice and Sprague-Dawley (SD) rats. Results: The chemical analysis of PBP showed that the main components of PBP were bile acids (BAs), especially glycochenodeoxycholic acid. There were no signs of toxicity observed in the acute oral test and the subchronic test. In the genotoxicity tests, no positive results were observed in the bacterial reverse mutation test. Additionally, in the mammalian micronucleus test and mouse spermatocyte chromosomal aberration test, no abnormal chromosomes were observed. In the teratogenicity test, no abnormal fetal development was observed. Conclusion: Our findings demonstrate that PBP, composed mainly of BAs, is non-toxic and safe based on the conditions tested in this study.